Long-term conservative management of symptomatic bladder endometriosis: A case series of 17 patients - Natsuki Nagashima; Tetsuya Hirata; Tomoko Arakawa; Kazuaki Neriishi; Hui Sun; Miyuki Harada; Yasushi Hirota; Kaori Koga; Osamu Wada-Hiraike; Yutaka Osuga (Elsevier, 2022)
Objectives: This study aimed to evaluate the course of long-term conservative management of bladder endometriosis (BE). Materials and methods: We retrospectively reviewed 17 cases of BE conservatively managed without surgery in our facility. The following factors were analyzed: age, medical history, lesion size, symptoms, hormonal treatment, and follow-up outcomes. Results: In this study, 15 patients received hormonal therapy and 2 did not. Oral contraceptive (OC), dienogest (DNG), and gonadotropin-releasing hormone agonist (GnRHa) were administered as the first regimen in 7, 5, and 3 patients, respectively. Of the 7 patients, OC administration was effective in alleviating urinary symptoms in all but 2 patients. Of 3 patients who received GnRHa, 2 switched to OC and then DNG, and 1 patient discontinued the treatment because of adverse effects. Of 5 patients who received DNG, all experienced symptom relief. DNG, OC, and GnRHa administration were effective and tolerable in 9 of 10 patients (90.0%), in 5 of 9 patients (55.6%), and in 2 of 3 patients (66.7%), respectively. In particular, 3 patients completed DNG treatment until menopause. The size of the BE lesion significantly decreased after 3 months of DNG administration, and the reduction effect was maintained until 48 months thereafter. Conclusion: This study proposed that hormonal therapy for BE is an effective option for those who are not planning to conceive or to undergo surgery. Specifically, DNG may be suitable for patients refusing surgery, considering the effectiveness and tolerance for long-term use.